Barriers to knowledge creation in community of practice - case study of AAA center - Jin, Ziguang (My University, 2009)
The main aims of this study were to explore knowledge creation process in community of practice (CoP), and find out barriers influences it. The theoretical part of this study was based on the literatures of knowledge creation, CoP and culture of knowledge management. A new SECI-CoP Knowledge Creation model was set up, based on SECI model and two typical CoP cases. The methodology used in this research was exploratory with a single case study, using qualitative research. By the interview of members of an online CoP, the CoP-Knowledge Creation model was tested, and eleven barriers of this case VCoP was found. This research provides a new perspective to the CoP research by exploring it with knowledge creation model. Both CoP and business process were taken as a whole in a complete SECI-CoP model, and this study provide an exploratory test in the Chinese case community. In this case, many barriers for community members to create knowledge are related to low activity phenomenon and face-to-face meeting phenomenon. This research initiatively took CoP as a knowledge creation platform and provides a new possibility of understanding meanings of CoP activities as knowledge creation tool. As well as that, this research also found out a challenging question of choosing SNS as a knowledge creation platform, and it requires more cross subject studies in the future
Keywords: Knowledge creation; community of practice; barriers; Chinese community; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|